Biodiesel production from waste cooking oil using calcium oxide/nanocrystal cellulose/polyvinyl alchohol catalyst in a packed bed reactor - Nor Azyan Farrah Adila binti Zik
Environmental problems and a shortage of conventional fossil fuel caused by the global consumption of fossil fuel have promoted the production of biodiesel from renewable resources. Biodiesel is produced from a chemical process of vegetable oil or animal fats and alcohol in the presence of a catalyst. Use of homogeneous catalyst indirectly produces a high amount of wastewater in order to purify the complex product from the reaction, and the catalyst is not reusable thus it is economically inviable. In the current work, biodiesel was synthesized from a reaction of waste cooking oil (WCO) and methanol in the presence of a catalyst which was derived from chicken bone and coconut residue in a packed bed reactor. Calcium oxide (CaO) was extracted from calcined chicken bone and nano-crystal cellulose (NCC) was isolated from coconut residue by acid hydrolyzed. CaO and NCC were supported by polyvinyl alcohol (PVA). The catalyst was analyzed using Fourier transform infrared (FTIR), Field emission scanning electron microscopy (FESEM), Thermogravimetric analysis (TGA) and X-ray diffraction (XRD) to study its elemental composition and surface morphology. The parameters used for the reaction were optimized by Design of Experiment (DOE) using Central Composite Design (CCD) of Response Surface Methodology (RSM) to produce maximum biodiesel yield. The maximum yield of 98.40 % was obtained at optimum temperature, methanol: oil and catalyst loading of 65 ⁰C, 6:1 and 0.5 wt% respectively. Evaluation of catalyst reusability indicated that it was reusable for four times while maintaining over 90 % of biodiesel yield. Investigation on the kinetic characteristics of the reaction specified that the reaction followed pseudo-first-order reaction with k-value ranged from 0.0092 min-1 to 0.0151 min-1 and the model was attested by Thiele modulus less than 2. The activation energy Ea observed for the transesterification reaction was 45.72 kJ/mol. Therefore, utilizing waste for biodiesel production of biodiesel can lower the production cost as well as help to save and clean the environment.